2020
DOI: 10.1002/ajmg.c.31843
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing for inherited eye conditions in over 6,000 individuals through the eyeGENE network

Abstract: Genetic testing in a multisite clinical trial network for inherited eye conditions is described in this retrospective review of data collected through eyeGENE ® , the National Ophthalmic Disease Genotyping and Phenotyping Network. Participants in eyeGENE were enrolled through a network of clinical providers throughout the United States and Canada. Blood samples and clinical data were collected to establish a phenotype:genotype database, biorepository, and patient registry. Data and samples are available for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
4
21
0
3
Order By: Relevance
“…If so, this would mirror prevalent observations in the genetics of psychological traits (Plomin & von Stumm, 2018): variation in each of them can be correlated with many thousands of genetic variants, so that even with extremely small and mostly nonsignificant individual effect sizes, collectively they account for a substantial proportion of trait variance. This would also be consistent with the increasing realization that most effect sizes are indeed very small in psychological research (Goetz et al, 2020). Small associations can be addressed with large samples and by testing nuances' collective associations with outcomes rather than focusing on individual trait-outcome associations.…”
Section: Nuancessupporting
confidence: 75%
See 1 more Smart Citation
“…If so, this would mirror prevalent observations in the genetics of psychological traits (Plomin & von Stumm, 2018): variation in each of them can be correlated with many thousands of genetic variants, so that even with extremely small and mostly nonsignificant individual effect sizes, collectively they account for a substantial proportion of trait variance. This would also be consistent with the increasing realization that most effect sizes are indeed very small in psychological research (Goetz et al, 2020). Small associations can be addressed with large samples and by testing nuances' collective associations with outcomes rather than focusing on individual trait-outcome associations.…”
Section: Nuancessupporting
confidence: 75%
“…For example, the associations are generally small in magnitude, particularly when the outcomes are not broad personality-like constructs themselves such as subjective well-being or self-esteem. Although small effect sizes are recognized as a general feature of psychological research, possibly for very good reasons (Goetz et al, 2020), the overall degrees to which outcomes are linked with personality differences may sometimes be underestimated because researchers have rarely explored ways of maximizing personality traits' predictive accuracy; this may require looking beyond the Big Few alone and focusing on the combined predictive value of many traits (Mõttus et al, 2020). Although the best possible prediction from a collection of variables does not necessarily correspond to the strongest possible individual trait-outcome associations because traits partly overlap, often it is exactly the overall degrees to which personality traits and outcomes are linked that researchers care about, rather than the effect sizes of individual traits.…”
Section: Domainsmentioning
confidence: 99%
“…Interestingly, 70% of resolved cases were deemed to have causative mutations in 20 genes only [ 82 ]. Similarly, in over 5000 pedigrees with genetic eye conditions from Canada and the US, 68% of pathogenic or likely pathogenic mutations were identified in just 10 genes [ 78 ]. Both of these large studies identified ABCA4 , USH2A and RPGR as the top three genes contributing to IRDs.…”
Section: Irds—target Panels and Whole Exome Studiesmentioning
confidence: 99%
“…The third and final section highlights translational research efforts to facilitate clinical trials for therapies directed at heritable human disorders. Two research registries in the United States, the National Ophthalmic Disease Genotyping Network (eyeGENE(R); Goetz et al, 2020) and the Foundation Fighting Blindness My Retina Tracker (FFB MRT; Mansfield et al, 2020), describe their respective experiences in large scale genetic testing and association of genotype–phenotype correlations in patient‐and provider‐submitted clinical data. Such registries are critical for better defining variant classification as pathogenic or benign, which in turn defines patient eligibility for gene‐directed therapies.…”
Section: Introductionmentioning
confidence: 99%